Dietary flavonoids: Nano delivery and nanoparticles for cancer therapy. (February 2021) - Aiello, Paola; Consalvi, Sara; Poce, Giovanna; Raguzzini, Anna; Toti, Elisabetta; Palmery, Maura; Biava, Mariangela; Bernardi, Marco; Kamal, Mohammad A.; Perry, George; Peluso, Ilaria
Abstract: Application of nanotechnologies to cancer therapy might increase solubility and/or bioavailability of bioactive compounds of natural or synthetic origin and offers other potential benefits in cancer therapy, including selective targeting. In the present review we aim to evaluate in vivo studies on the anticancer activity of nanoparticles (NPs) obtained from food-derived flavonoids. From a systematic search a total of 60 studies were identified. Most of the studies involved the flavanol epigallocatechin-3-O-gallate and the flavonol quercetin, in both delivery and co-delivery (with anti-cancer drugs) systems. Moreover, some studies investigated the effects of other flavonoids, such as anthocyanins aglycones anthocyanidins, flavanones, flavones and isoflavonoids. NPs inhibited tumor growth in both xenograft and chemical-induced animal models of cancerogenesis. Encapsulation improved bioavailability and/or reduced toxicity of both flavonoids and/or co-delivered drugs, such as doxorubicin, docetaxel, paclitaxel, honokiol and vincristine. Moreover, flavonoids have been successfully applied in molecular targeted nanosystems. Selectivity for cancer cells involves pH- and/or reactive oxygen species-mediated mechanisms. Furthermore, flavonoids are good candidates as drug delivery for anticancer drugs in green synthesis systems. In conclusion, although human studies are needed, NPs obtained from food-derived flavonoids have promising anticancer effects in vivo .